2009
DOI: 10.1038/ng.507
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide perspective of genetic variation in human metabolism

Abstract: Serum metabolite concentrations provide a direct readout of biological processes in the human body, and are associated with disorders such as cardiovascular and metabolic diseases. Here we present a genome-wide association study with 163 metabolic traits using 1809 participants from the KORA population, followed up in the TwinsUK cohort with 422 participants. In eight out of nine replicated loci (FADS1, ELOVL2, ACADS, ACADM, ACADL, SPTLC3, ETFDH, SLC16A9) the genetic variant is located in or near enzyme or sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
656
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 612 publications
(688 citation statements)
references
References 25 publications
26
656
2
4
Order By: Relevance
“…Genome-wide association studies have shown a strong association of genetic SPTLC3 variants with alterations in lipid metabolism [29] and increased risk for myocardial infarction [30]. Therefore, lower C 16 SO levels might be directly or indirectly related to the increased risk of diabetic patients for developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have shown a strong association of genetic SPTLC3 variants with alterations in lipid metabolism [29] and increased risk for myocardial infarction [30]. Therefore, lower C 16 SO levels might be directly or indirectly related to the increased risk of diabetic patients for developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the strength of the observed associations is so great that they easily overcome the multiple-testing corrections necessitated by the large number of parallel GWASs inherent in metabolome-wide studies. Ceramide synthesis and transport Gieger et al 2008;Illig et al 2010;Nicholson et al 2011;Suhre et al 2011Genes Nutr (2013 A comparison of these recent studies to those on favism and lactose intolerance discussed above indicates how dramatically gene-metabolism research has changed over the past decade and a half. In the past, linking variations in metabolism to a specific gene was often the endpoint of extensive mechanistic and epidemiological studies.…”
Section: Holistic Metabolomics Phenotypes In Gwasmentioning
confidence: 99%
“…A number of genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the chromosome 6 region that includes ELOVL2 to be strongly associated with plasma fatty acid proportions (Aulchenko et al 2009;Sabatti et al 2009;Tanaka et al 2009;Illig et al 2010). A subsequent meta-analysis confirmed a number of minor allele associations with higher EPA and DPA and lower DHA proportions (Lemaitre et al 2011).…”
Section: Introductionmentioning
confidence: 99%